Comparative Safety of Dipeptidyl Peptidase-4 Inhibitors Versus Sulfonylureas and Other Glucose-lowering Therapies for Three Acute Outcomes. Issue 1 (December 2018) - Gamble, John-Michael; Donnan, Jennifer; Chibrikov, Eugene; Twells, Laurie; Midodzi, William; Majumdar, Sumit
Abstract Although the glucose lowering effect of dipeptidyl peptidase-4 (DPP4) inhibitors is well established, several potential serious acute safety concerns have been raised including acute kidney injury, respiratory tract infections, and acute pancreatitis. Using the UK-based Clinical Practice Research Datalink (CPRD), we identified initiators (365-day washout period) of DPP4 inhibitors and relevant comparators including initiators of sulfonylureas, metformin, thiazolidinediones, and insulin between January 2007 and January 2016 to quantify the association between DPP4 inhibitors and three acute health events – acute kidney injury, respiratory tract infections, and acute pancreatitis. The associations between drug and study outcomes were estimated using Cox proportional hazard models adjusted for deciles of high-dimensional propensity scores and number of additional glucose lowering agents. After controlling for potential confounders, the risk was not significantly increased or decreased for initiators of DPP4 inhibitors compared to sulfonylureas (hazard ratio (HR) [95% confidence interval (CI)] for acute kidney injury: 0.81 [0.56–1.18]; HR for respiratory tract infections: 0.93 [0.84–1.04]; HR for acute pancreatitis 1.03 [0.42–2.52], metformin (HR for respiratory tract infection 0.91 [0.65–1.27]), thiazolidinediones (HR for acute kidney injury: 1.12 [0.60–2.10]; HR for respiratory tract infections: 1.02 [0.86–1.21]; HR for acute pancreatitis: 1.21 [0.25–5.72]), or insulin (HR for acute kidney injury: 1.40 [0.77–2.55]; HR for respiratory tract infections: 0.74 [0.60–0.92]; HR for acute pancreatitis: 1.01 [0.24–4.19]). Initiators of DPP4 inhibitors were associated with an increased risk of acute kidney injury when compared to metformin initiators (HR [95% CI] for acute kidney injury: 1.85 [1.10–3.12], although this association was attenuated when DPP4 inhibitor monotherapy was compared to metformin monotherapy exposure as a time-dependent variable (HR 1.39 [0.91–2.11]). Initiation of a DPP4 inhibitor was not associated with an increased risk of acute kidney injury, respiratory tract infections, or acute pancreatitis compared to sulfonylureas or other glucose-lowering therapies.